Largely underestimated production of isoprene epoxydiols (IEPOX) through high-NO oxidation pathways in urban areas - Sainan Wang; Mike J. Newland; Andrew R. Rickard; Jacqueline F. Hamilton; Thomas J. Bannan; Archit Mehra; Carl J. Percival; Freya A. Squires; Weiwei Hu; Wei Song; Yang Chen; Xiaoling Zhang; et al. (npj Climate and Atmospheric Science)
Abstract Isoprene is the dominant nonmethane volatile organic compound (VOC) emitted into the atmosphere globally, with important atmospheric chemistry impacts on air quality and climate. One crucial intermediate in its gas-phase oxidation is isoprene epoxydiol (IEPOX), which contributes significantly to the formation of secondary organic aerosols (SOA). It is generally accepted that IEPOX is efficiently formed in remote forested regions with a sufficiently low NO/HO2 ratio. Here, we show that the oxidation of isoprene hydroxynitrates (IHN) can be an alternative, efficient, NO-driven pathway leading to the formation of IEPOX in urban areas where moderate to high NO concentrations exist. Field measurements from the megacity of Beijing show that this pathway contributes to more than 50% of IEPOX production during the morning and early afternoon. The results improve our understanding of the NOx dependence of SOA formation in polluted areas, where anthropogenic emissions can significantly enhance biogenic SOA formation.